Peran pemerintah Kota Batu dalam implementasi kebijakan pembangunan pariwisata berdasarkan paradigma pembangunan berkelanjutan (sustainable development) - Asih Widi Lestari; Firman Firdausi (Masyarakat, Kebudayaan dan Politik, 2017)
Indonesia is a country with rich and diverse natural resources. Batu is a city in Indonesia which popular because of its tourism potential. In the effort to develop the tourism, the Government of Batu designed several tourism policies. In tourism development, Government of Batu refer to sustainable development. This article tries to describe and analyze the role of Government of Batu to implement the tourism development policy based on the sustainable development paradigm. Research method used is descriptive qualitative using primary and secondary data. Data gathered through observation, interview, and documentation. This research found that the implementation of tourism policy in Batu has met the principles of sustainable development namely, economic welfare, sustainable environment, social justice, and living environment oriented. The Government of Batu plays significant role in creating the policy in general and regulating permissions, implementing prosociety policy and controlling private sectors investment in Batu.